PENGARUH INTENSITAS PENGGUNAAN TIKTOK TERHADAP MORAL SISWA DI SEKOLAH MENENGAH ATAS NEGERI 7 TEBO - Selfi Septiawati; Rina Juliana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This thesis aims to determine the effect of TikTok usage on student morals at State Senior High School 7 Tebo. The background to this research is the occurrence of moral decadence, such as laziness in congregational Dhuhr prayers at the prayer room, rudeness to fellow students, disrespect for teachers, and a tendency to lie. This research is a quantitative research with a quantitative correlation research type. The sample of this study consisted of 64 students, which was calculated using the Slovin formula with a 10% error rate. Sampling was carried out randomly in each class with a population of 180 students. Data collection was carried out through questionnaires and documentation. Data analysis carried out was a statistical test, namely the normality test, homogeneity test, linearity test, correlation test, t-test, and f-regression test using the SPSS version 26 program to determine the relationship between the two variables. Based on the research results and discussion, the following conclusion can be drawn: there is a relationship between the use of TikTok and student morals. This is indicated by the results of the t-test obtained a value of 2.418 > 1.670 or in other words, t count > t table with a significance value obtained of 0.019 < 0.05, which means Ha is accepted. Thus, it can be concluded that the use of TikTok has an effect on changes in student morals at SMA Negeri 7 Tebo, but this influence is not absolute because there are still other factors that influence student morals.